DYNAMICS OF SOCIAL INEQUALITIES IN THE FACE OF MACROECONOMIC SHOCKS IN MOROCCO: AN ECONOMETRIC ANALYSIS USING THE MODEL ARDL - DFOUF, Sanaa; HAMDI, Fekkak; CHAROUK, Tarik; FAIDI, Abdelhak (Journal of Ecohumanism, 2025)
This article evaluates the relationship between macroeconomic shocks and social inequalities in Morocco through the lens of the ARDL model. It uses annual information on GDP, unemployment, and inflation and social spending in order to analyzed social inequalities manifested by the Gini index.Empirical studies suggest that the economic growth has ambiguous consequences on inequality, as its resource mobilization tendency on one hand leads to a long term decrease in income disparity. Furthermore, unemployment and inflation are negative determinants of inequalities, specifically targeting the lower most household. On the other hand, social transfers do help mitigate inequality, even though their effect is virtually nonexistent in the absence of any form of redistribution.The econometric findings indicate a long run co-integration of the variables which in effect means that there are persistent inequalities over time which tend to be influenced by the macro shock incidence. This strengthens the urgency for comprehensive economic strategies that incorporate active labor market policies and social services to counter inequalities.In conclusion, this study appeals for increased attention towards redistributive policies alongside implementable economic strategies that can soften the impact of macroeconomic shocks on social inequalities in Morocco.